Assessing Learning Management System (LMS) for The Dairy Farmer: Obstacles to Delivering Online Learning Content - Citra Kurniawan; Otto Fajarianto; Ifit Novita Sari; Tri Candra Wulandari; Ena Marlina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
Online learning is currently an alternative learning strategy for continuous learning amidst the limitations of face-to-face learning due to the spread of the Covid-19 outbreak. However, the implementation of online learning certainly does not only provide solutions but also provides obstacles in its implementation which results in the non-delivery of learning content in online learning. Of course this can have an impact on dairy farmers as new users of the Learning Management System. This study aims to analyze the constraints of online learning based on the responses that have been shared by Twitter social media users towards the implementation of online learning and to assess the use of LMS for dairy farmers. This study uses the Twitter data crawling method on Twitter social media user responses to the topic of online learning constraints and data visualization to analyze LMS usage by . The research findings state that most users of online learning complain about internet quota constraints and the technical constraints experienced by them resulting in learning content not being absorbed optimally. This research can enrich research related to the use of social media data as data that can be analyzed and documented for learning development.